Status of Analgesic Drugs and Quality of Life Results for Diabetic Peripheral Neuropathy in China - Lian, Jingxuan; Wang, Haijun; Cui, Rongrong; Zhang, Chaoxia; Fu, Jianfang (Frontiers in Endocrinology, 2022)
Abstract: Objective: The purpose of this study is to describe the current clinical situation of patients with painful diabetic peripheral neuropathy (DPN) and related anxiety, depression, and the quality of life of patients in mainland China, and to report the current status of the use of analgesics. Methods: Between June 15, 2021 and October 15, 2021, a total of 401 participants participated in the study. Recruitment was carried out using a multi-level sampling method. Participants' demographics, medical history, analgesic use, Michigan Symptom Score (MNSI), Numerical Rating Scale (NRS) pain score, Patient Health Questionnaire 9 (PHQ-9) score, Generalized Anxiety Disorder 7 (GAD) -7) Score, quality of life score (SF-12) and diabetes treatment status were collected. Results: Among the participants, there were 236 male patients and female patients. Participants were 322 patients over 40 years old. Regarding the use of analgesics: 132 patients reported using analgesics, 221 patients reported not using analgesics, and 48 patients reported having used analgesics. The results of the scale showed that the scores of NRS, GAD-7, PHQ-9 and SF-12 were 5.12 ± 2.15, 6.33 ± 3.67, 8.46 ± 4.07 and 47.84 ± 19.92 for patients who used analgesics, Compared with patients who did not use analgesics(NRS: 1.99 ± 1.7, GAD-7: 1.81 ± 2.81, PHQ-9: 3.13 ± 4.10, SF-12: 78.34 ± 21.66) there are significant differences (p< 0.001). In addition, patients’ NRS scores are also closely related to GAD-7, PHQ-9 and SF-12 scores. Conclusion: The severity of symptoms, mental status and quality of life of patients who used analgesics were more severe than those of patients who did not use analgesics. Pregabalin is still the preferred analgesic for patients with painful DPN, and the use of opioids in my country is extremely low, which is consistent with current international guidelines. Age, diabetic duration, DPN duration, PHQ-9 score, GAD-7 score and SF-12 scores are closely related to NRS pain scores. In addition, there are still a considerable number of patients who have not used analgesics due to financial burdens and other reasons, suggesting that China still has insufficient pain management in DPN patients.